Marker-assisted selection for quantitative traits - Schuster,Ivan (2011)
Although thousands of scientific articles have been published on the subject of marker-assisted selection (MAS) and quantitative trait loci (QTL), the application of MAS for QTL in plant breeding has been restricted. Among the main causes for this limited use are the low accuracy of QTL mapping and the high costs of genotyping thousands of plants with tens or hundreds of molecular markers in routine breeding programs. Recently, new large-scale genotyping technologies have resulted in a cost reduction. Nevertheless, the MAS for QTL has so far been limited to selection programs using several generations per year, where phenotypic selection cannot be performed in all generations, mainly in recurrent selection programs. Methods of MAS for QTL in breeding programs using self-pollination have been developed.